Child Labor - Christopher Udry (Yale University, Economic Growth Center, 2003)
Child labor exists because it is the best response people can find in intolerable circumstances. Poverty and child labor are mutually reinforcing: because their parents are poor, children must work and not attend school, and then grow up poor. Child labor has two important special features. First, when financial markets are imperfect, the separation in time between the immediate benefits and longdelayed costs of sending children to work lead to too much child labor. Second, the costs and benefits of child labor are borne by different people. Targeted subsidies for school attendance are very effective in reducing child labor because they successfully address both of these problems.
Keywords: J24; O15; 330; child labor; human capital; household economics; Kinderarbeit; Armut; Bildungsverhalten; Bildungspolitik; Entwicklungsländer